2022
DOI: 10.3390/su14137919
|View full text |Cite
|
Sign up to set email alerts
|

Is Implementing a Biotech Ban Correct or Not? Analysis of Farmer Perceptions and Attitudes on the Philippine Supreme Court’s Ban on Biotech Crops

Abstract: Several studies have explored the effects of restrictive policies in different case-use instances; however, studies focusing on restrictive agricultural policies and their effects on major stakeholders are scarce. While the Philippines has been increasing its support for biotech-related technologies in agriculture, such as the recent approval of Golden Rice and Bt (Bacillus thuringiensis) eggplant for cultivation, the years prior to 2020 have not been as lenient in the acceptance of biotech crops. This paper e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…On the negative side, the farmers are emphasizing that while ECA's adoption is possible, it does not currently present economic merits. Several studies have already established that farm income can enhance farmers' adoption of agricultural technologies [71][72][73]. In this case, some farmers are saying that the repercussions of using fewer or no chemical fertilizers are the increase in farming expenses and labor.…”
Section: Eca's Environmental and Economic Sustainabilitymentioning
confidence: 99%
“…On the negative side, the farmers are emphasizing that while ECA's adoption is possible, it does not currently present economic merits. Several studies have already established that farm income can enhance farmers' adoption of agricultural technologies [71][72][73]. In this case, some farmers are saying that the repercussions of using fewer or no chemical fertilizers are the increase in farming expenses and labor.…”
Section: Eca's Environmental and Economic Sustainabilitymentioning
confidence: 99%
“…However, to ensure the long-term sustainability of ECA, it is crucial to ensure its economic viability for farmers (FAO, 2017). Indeed, several studies have already emphasized that farm income can increase farmers' adoption of agricultural technologies (Brooks et al, 1986;Gonzalvo et al, 2022;Gonzalvo et al, 2020); therefore, ECA practices should not lead to financial losses or negatively impact farmers' income. For instance, in the study conducted by Maharjan et al (2022) among ECA farmers in Fujioka, Japan, they reported that making profit is among the top priorities of farmers, aside from making positive contributions to environmental conservation.…”
Section: Economic Sustainability Of Ecamentioning
confidence: 99%
“…Indeed, several studies have already emphasized that farm income can increase farmers' adoption of agricultural technologies (Brooks et al, 1986;Gonzalvo et al, 2022;Gonzalvo et al, 2020); therefore, ECA practices should not lead to financial losses or negatively impact farmers' income. For instance, in the study conducted by Maharjan et al (2022) among ECA farmers in Fujioka, Japan, they reported that making profit is among the top priorities of farmers, aside from making positive contributions to environmental conservation. One of the farmers in that study said that: "As a producer, if you can't make a profit, then your farming method is not sustainable.…”
Section: Economic Sustainability Of Ecamentioning
confidence: 99%